Budżet przepływów środków pieniężnych w państwowej szkole wyższej a zasada kontynuacji działania - Ćwiąkała-Małys, Anna (The Budget of Liquid Asset in a Higher State School and/vs the Activity Continuation Rule, 2007)
The aim of this article is to justify the necessity to create the budget of liquid asset. The author claims that a correct preparation of it enables people to generate information. Due to this information it is possible to control the situation of cash flow. The article also shows a thorough ratio analysis of liquidity based on 10 higher state schools between 2003 and 2005.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 67-85